Innate immunity and gut-microbe mutualism in Drosophila. - Ryu, J.H.; Ha, E.M.; Lee, W.J. (Developmental and Comparative Immunology, 2010)
Metazoan guts face a wide variety of microorganisms upon exposure to the environment, including beneficial symbionts, non-symbionts, food-borne microbes and life-threatening pathogens. Recent evidence has shown that the innate immunity of gut epithelia, such as anti-microbial peptide- and reactive oxygen species-based immune systems, actively participate in gut-microbe homeostasis by shaping the commensal community while efficiently eliminating unwanted bacteria. Therefore, elucidation of the regulatory mechanism by which gut innate immunity occurs at the molecular level will provide a novel perspective of gut-microbe mutualisms as well as of gut diseases caused by alterations in the innate immunity.